Optical Bistability 1981
DOI: 10.1007/978-1-4684-3941-0_25
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Plane Wave Reflection and Refraction by the Nonlinear Interface

Abstract: This report includes a review of published as well as recent results. In previous papers a new kind of optical bistability was proposed which is connected with reflection and refraction of light by a single surface on a nonlinear medium without a resonator or feedback; its first experimental observations were made recently by Smith et al. The main conditions required for its existence are very exact matching of the optical densities of both media and almost grazing incidence of light. These effects are availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This constitutes an additional condition in our L-NL-L problem. , A h squares are expressed through 0 ε ε = value at boundaries by formula (1). Therefore, the parameter cnst can be expressed in terms of 0 ε ε…”
Section: Formulation Of a Boundary Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…This constitutes an additional condition in our L-NL-L problem. , A h squares are expressed through 0 ε ε = value at boundaries by formula (1). Therefore, the parameter cnst can be expressed in terms of 0 ε ε…”
Section: Formulation Of a Boundary Conditionmentioning
confidence: 99%
“…A h 0 ε = and find its roots ( 1, 2) ε ε ; integrating over ( 1,2) ε ε we get the half-period z / 2 λ ; integrating over 1 ( 1,0 ) ε ε we get the off-shoot length we collect enough data for smooth interpolation.…”
Section: Family Of Asymmetric Wave Pieces Satisfying Boundary Conditi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Kaplan who suggested that bistability can be formed by the reflection of light near the critical angle from an interface separating a linear and a nonlinear medium [58][59]. Two years later, Smith et al [60] reported on the first optical device operated based on the intensity-dependent total internal reflection.…”
Section: Introduction To Optical Bistable Devicesmentioning
confidence: 99%
“…Dielectric function equation. Wave propagation in media with intensity-dependent dielectric permittivity has been long at the center of the attention of many researchers [2,3,4] to name a few. From this class of problems, the TM-wave scattering case is particularly difficult.…”
mentioning
confidence: 99%